PARADIGMA BARU MEMAHAMI TEOLOGI DAN PENDIDIKAN KRISTEN KORELASI TEKS KOLOSE 3:2 DENGAN ERA DISRUPSI - Stenly R. Paparang (Phronesis: Jurnal Teologi dan Misi, 2020)
The fact that the era of disruption creates many changes and shifts in various fields, urges certain parties in the educational environment to quickly adapt and even create breakthroughs in maintaining the substance of Christian theology and education through online application-based media. Changes in the learning process from face-to-face to online result in a variety of benefits as well as prudence. On the one hand online learning is not limited to space and time, and on the other hand forces certain parties to meet the demands of such learning. In the church environment also experienced the same thing. The process of personalization became online. Thus, the paradigm shift in Christian theology and education is an inescapable fact. Efforts to think of spiritual matters become a continuing responsibility, no matter what the situation. Disruption era shows the rise of online-based social media. Nevertheless, believers are encouraged to use it as a place to preach the gospel of Jesus Christ as a confirmation of the attitude of believers who think about the above. This article uses a library study method with an exegetic-correlational approach that explains the meaning of text in the frame of correlation with disruption era.